Antiplatelet and Antithrombotic Effects of Epimedium koreanum Nakai. (17th April 2021) - Irfan, Muhammad; Kwon, Tae-Hyung; Lee, Dong-Ha; Hong, Seung-Bok; Oh, Jae-Wook; Kim, Sung-Dae; Rhee, Man Hee
Abstract : Background and Objective . Epimedium koreanum Nakai is a medicinal plant known for its health beneficial effects on impotence, arrhythmia, oxidation, aging, osteoporosis, and cardiovascular diseases. However, there is no report available that shows its effects on platelet functions. Here, we elucidated antiplatelet and antithrombotic effects of ethyl acetate fraction of E. koreanum . Methodology . We analyzed the antiplatelet properties using standard in vitro and in vivo techniques, such as light transmission aggregometry, scanning electron microscopy, intracellular calcium mobilization measurement, dense granule secretion, and flow cytometry to assess integrin α IIb β 3 activation, clot retraction, and Western blot, on washed platelets. The antithrombotic effects of E. koreanum were assessed by arteriovenous- (AV-) shunt model in rats, and its effects on hemostasis were analyzed by tail bleeding assay in mice. Key Results . E. koreanum inhibited platelet aggregation in agonist-stimulated human and rat washed platelets, and it also reduced calcium mobilization, ATP secretion, and TXB2 formation. Fibrinogen binding, fibronectin adhesion, and clot retraction by attenuated integrin α IIb β 3 -mediated inside-out and outside-in signaling were also decreased. Reduced phosphorylation of extracellular signal-regulated kinases (ERK), Akt, PLC γ 2, and Src was observed. Moreover, the fraction inhibited thrombosis. HPLC results revealed that the fraction predominantly contained icariin. Conclusion and Implications . E. koreanum inhibited platelet aggregation and thrombus formation by attenuating calcium mobilization, ATP secretion, TXB2 formation, and integrin α IIb β 3 activation. Therefore, it may be considered as a potential candidate to treat and prevent platelet-related cardiovascular disorders.